Brominated indoles from a marine mollusc inhibit inflammation in a murine model of acute lung injury - Ahmad, Tarek B. (PLoS One, 2017)
New drug leads for the treatment of inflammation are urgently needed. Marine molluscs are widely used as traditional medicines for the treatment of inflammation. Here we report the positive effects of a hypobranchial gland (HBG) extract and the dominant bioactive compound 6-bromoisatin from the Muricidae mollusc Dicathais orbita, for reducing lipopolysaccharide (LPS) induced acute lung inflammation in a mouse model. Both 6-bromoisatin and the HBG extract suppressed the inflammatory response in mice that were pre-treated by oral gavage at 48, 24 and 1 h prior to LPS infusion. The inflammatory antagonists were tested at concentrations of 0.5 mg/g and 0.1 mg/g HBG extract and 0.1 mg/g and 0.05 mg/g 6-bromoisatin in carrier oil and all treatments reduced inflammation as indicated by a significant suppression of inflammatory markers present in bronchoalveolar lavage fluid (BALF), in comparison to LPS induced positive control mice administered the carrier oil alone (p < 0.0001). Tumour necrosis factor-alpha (TNFα) and interleukin-1 beta (IL-1β) levels, in addition to total protein concentration were all significantly reduced in BALF from mice treated with the extract or 6-bromoisatin. Furthermore, all treatment groups showed significant reductions in neutrophil sequestration and preservation of the lung tissue architecture compared to the positive control (p < 0.0001). The combined results from this study and our previous in vitro studies indicate that 6-bromoisatin in the HGB extracts inhibit the activation of inflammatory signalling pathway. The results from this study further confirm that the HBG extract from Muricidae molluscs and 6-bromoisatin are bioavailable and effective in vivo, thus have potential for development as natural therapeutic agents for inflammation.